Tecnologia educacional e possibilidades construtivistas a partir da percepção dos alunos sobre os processos de aprendizagem no curso superior a distância de tecnologia em gestão de turismo - CEFET-RJ / CEDERJ - Damas, Helton Luiz Gonçalves (2013)
This paper aims to analyze how students from Course of Technology in Tourism Management evaluates the operating platform moodle seeking to prove the relationship between education and technology in accordance with the Critical Theory of Technology from Feenberg. Andrew Feenberg is one of the pioneers of distance education to create a course based on this modality in the 1980s and since then studies the distance education with relation of social studies of science and technology and his research is based on technological constructivism. Thus, the state government of Rio de Janeiro in 2000 created the CEDERJ - Center for Distance Higher Education in Rio de Janeiro - a consortium of six public universities of Rio de Janeiro. Among the courses offered by CEDERJ, can highlight the Course of Technology in Tourism Management, administered by the Federal Center for Technological Education Celso Suckow da Fonseca (CEFET / RJ). Since it is the first half of the course students have difficulties in dealing with learning technologies, and relevant to assess the perceptions that they have on the learning processes and to analyze the possibilities of student participation in the building of moodle platform, molding according to the interests of all actors involved in the course - the governing, teachers and students. As methodology, the work is a case study based on qualitative and quantitative research, data obtained through a questionnaire on line targeted at students from the five centers of the course. After interpretation and data analysis it became clear what was the perception that students have about the learning processes of the course. As a result, we can verify that students have sense evaluative notes relevant to achieving satisfactory with respect to the learning process in which they are inserted and they can constitute social agents capable of modifying educational technology.